Ultrasonic extraction of antioxidant compound from red pitaya - Muhammad Shahairie, Abdul Razak (2009)
The health benefit of antioxidant’s activities from the betacyanin contents in red Pitaya, attract a lot of interest from the public, food as well as pharmaceutical industries. This natural antioxidant from red Pitaya can replace the dangerous synthetic antioxidant at the market. The works done in this research explore the effects of different process parameter on antioxidant yield via ultrasonic extraction method. The extracted oil was recovered using rotary evaporator and the composition of vitamin C was determined using HPLC. The parameter studied were different solid to solvent ratio (10 gram dried red Pitaya with 30 ml ethanol, 10 gram dried red Pitaya with 50 ml ethanol, 10 gram dried red Pitaya 200 ml ethanol, 10 red Pitaya with 250 ml ethanol), different ultrasonic power (150 watt, 200 watt, 250 watt, 300 watt), and different sonification time (20 minute, 30 minute, 50 minute, 60 minute). For the control sample, sample has been put into solvent without ultrasonic extraction. The analysis show that there is no antioxidant has been detected during the experiment. Results demonstrate that the highest value of vitamin C in first parameter is 6.16380 mg/L at 10 gram of dried red Pitaya with 250 ml ethanol. Besides, the vitamin C recovery was 6.88542 mg/L obtained by using second parameter with 10 gram of dried red Pitaya and 250 ml ethanol. The best yield of vitamin C obtained was 7.13589 mg/L by using both of the best parameter which were (state what is the parameter) with different sonification time for about 50 minutes of ultrasonic extraction at 10 gram sample with 50 solvent and 300 watt.